1989
DOI: 10.1113/jphysiol.1989.sp017736
|View full text |Cite
|
Sign up to set email alerts
|

On the multiple‐conductance single channels activated by excitatory amino acids in large cerebellar neurones of the rat.

Abstract: 3. From the relative areas under current amplitude histograms it was estimated that the percentage of openings with conductances greater than 30 pS was about 83 % with NMDA, 79 % with glutamate and 78 % with aspartate. In some patches, the majority of > 30 pS events evoked by these agonists were to the maximum conductance of 48 pS, whereas in other patches there were more 38 pS openings than 48 pS openings. Only 27 % of quisqualate openings, and about 10 % of kainate openings, were > 30 pS.4. Of the small ampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
62
1
1

Year Published

1991
1991
2009
2009

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 45 publications
11
62
1
1
Order By: Relevance
“…Pentobarbitone did not alter the reversal potential. Noise analysis As previously reported by Ascher et al (1988), Cull-Candy et al (1988) and Cull-Candy & Usowicz (1989), application of NMDA and other glutamate agonists is accompanied by an increase in signal noise. The plots of noise variance against mean current were linear (not shown) suggesting that the open probability was low and the single channel conductance estimated from the variance of the current noise was 45 + 3 pS and it was not altered by co-application of the anaesthetic (100-400 gM).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Pentobarbitone did not alter the reversal potential. Noise analysis As previously reported by Ascher et al (1988), Cull-Candy et al (1988) and Cull-Candy & Usowicz (1989), application of NMDA and other glutamate agonists is accompanied by an increase in signal noise. The plots of noise variance against mean current were linear (not shown) suggesting that the open probability was low and the single channel conductance estimated from the variance of the current noise was 45 + 3 pS and it was not altered by co-application of the anaesthetic (100-400 gM).…”
Section: Resultsmentioning
confidence: 86%
“…Unlike nictonic receptors which have relatively simple kinetics, NMDA receptors have multiple open and closed states (Gibb & Colquhoun, 1992). Openings occur in bursts and clusters and they have multiple conductance levels (Cull-Candy & Usowicz, 1989). The effects of anaesthetics on such intricate gating poses a number of interesting problems: Is it possible to describe the effects of an anaesthetic on NMDA receptors in terms of a simple kinetic model?…”
Section: Introductionmentioning
confidence: 99%
“…In radioligand binding studies of non-NMDA receptors, chaotropic ions increased the specific binding of [3H]-AMPA in rat brain membranes by up to 800% of basal binding at concentrations ranging from 1-100mM (Honore & Nielsen, 1985;Murphy et al, 1987;Olsen et al, 1987;Honore & Drejer, 1988;Nielsen et al, 1988;Shahi & Baudry, 1992 (Shahi & Baudry, 1992 the AMPA response at a greater level of desensitization since it was markedly enhanced by Con-A treatment, whereas Ip was relatively insensitive . In addition, a study of the single channel currents activated by quisqualate on hippocampal neurones, revealed that Ip may be carried by rapidly-inactivating high conductance channels (single channel conductance (7) = 35pS; Tang et al, 1989), whereas the maintained current (approximating to ISS) was carried mostly by low conductance channels (y = 8pS; Jahr & Stevens, 1987;Cull-Candy & Usowicz, 1987;Ascher & Nowak, 1988 Ascher & Nowak, 1988).…”
Section: Resultsmentioning
confidence: 99%
“…1990) and in cultures of synaptically connected hippocampal neurones (Lester, Clements, Westbrook & Jahr, 1990) (Cull-Candy & Usowicz, 1987;Jahr & Stevens, 1987;Ascher, Bregestowski & Nowak, 1988), the mean open time cannot be the 'elementary event' that determines the decay of NMDA EPSCs. However, the activity of NMDA receptor channels in outside-out patches tends to appear in clusters lasting hundreds of milliseconds (Jahr & Stevens, 1987;Howe, Colquhoun & Cull-Candy, 1988;Keller et al 1991) even after pulse-like applications of agonist (Lester et al 1990).…”
Section: Discussionmentioning
confidence: 99%